The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/jat.4042
|View full text |Cite
|
Sign up to set email alerts
|

A pH‐responsive polymer linked with immunomodulatory drugs: synthesis, characteristics and in vitro biocompatibility

Abstract: Cancer immunotherapy is a promising method for cancer therapy. Imiquimod (R837) is a molecule that could activate immune systems for cancer immunotherapy, but an easily manufactured biocompatible carrier to deliver R837 may be needed to overcome the disadvantages of R837. Micelles formed by biocompatible copolymers have been widely used to deliver chemotherapeutic drugs but not immunotherapeutic drugs. In this study, R837 was linked to an amphiphilic biodegradable copolymer mPEG‐b‐PLA via acid‐sensitive Schiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…This is also consistent with previous studies that showed that the presence of metal‐based NPs or metal ions alleviated the toxicity of other NPs (Hackenberg et al, 2017; Hernández‐Moreno et al, 2016; Hu, Hu, Li, & Zhao, 2016; Sun et al, 2020). However, we noticed that compared with soft materials such as liposomes (L. Shi, Wang, et al, 2020), polymers (Li et al, 2021; Zhou et al, 2020), chitosan (W. Han et al, 2019), lipids (Wan et al, 2018; Xie, Wan, Chen, Han, & Wang, 2020), soluble supramolecular NPs (X. Chen, Hu, et al, 2020), and proteins (An et al, 2020), the cytotoxicity of Ag–ZnO nanocomplexes was still relatively high. Nevertheless, the results from this study suggested that development of novel nanocomplexes might be a plausible way to reduce the toxicity of ZnO NPs.…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with previous studies that showed that the presence of metal‐based NPs or metal ions alleviated the toxicity of other NPs (Hackenberg et al, 2017; Hernández‐Moreno et al, 2016; Hu, Hu, Li, & Zhao, 2016; Sun et al, 2020). However, we noticed that compared with soft materials such as liposomes (L. Shi, Wang, et al, 2020), polymers (Li et al, 2021; Zhou et al, 2020), chitosan (W. Han et al, 2019), lipids (Wan et al, 2018; Xie, Wan, Chen, Han, & Wang, 2020), soluble supramolecular NPs (X. Chen, Hu, et al, 2020), and proteins (An et al, 2020), the cytotoxicity of Ag–ZnO nanocomplexes was still relatively high. Nevertheless, the results from this study suggested that development of novel nanocomplexes might be a plausible way to reduce the toxicity of ZnO NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Under acidic conditions, an accelerated release of R837 from micelles was observed. In RAW264.7 macrophages, R837-loaded micelles stimulate the expression of MHC II-stimulating molecules at pH 6.5, but not at physiologic pH [ 71 ].…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…2,3 Chemotherapy, as one of the three main therapies, is limited by toxic and side effects to normal cells and drug resistance of cancer cells [4][5][6] because of the low concentration of effective drugs in the tumor area. 7 Therefore, effectively improving the targeting of anti-tumor drugs to tumor tissues and controlling the release of drugs have become the focus of contemporary medical research. 8 Smart drug-loaded nanocarriers, also called stimulusresponsive or environment-responsive drug-loaded nanocarriers, have attracted widespread attention and research.…”
Section: Introductionmentioning
confidence: 99%